(untitled) (International Conference on Computers in Education, 2020)
This paper describes an intervention piloted in secondary schools in Singapore in the second half of 2020, in response to the COVID-19 pandemic. The intervention aims to afford learners more authentic understandings of the need to invest effort and self-discipline in nurturing the new habit of practicing safe-distancing, beyond just doing so because of public exhortation. It seeks to achieve this objective through two complementary halves, the first being an activity within a virtual environment during which a (virtual) virus is diffusing, and the second being dialogue and discussion around students’ decision-making and behaviours, as informed from an analysis of data of interaction from the first half, via a web-based interface. In this way, the Socially Responsible Behaviour through Embodied Thinking (SORBET) Project represents not only an intervention designed to meet the challenges to learning imposed by COVID-19, but also one of the current few which attempt to do so by leveraging students’ evolving conceptions about the diffusion of a virus amongst a population. Understood thusly, the intervention has potential curricular applications in a number of disciplinary domains, such as in mathematics, geography, biology and citizenship education.